Concordances linguistiques entre aires celtique et romane à partir des données des atlas multilingues - Daniel Le Bris; Elisabetta Carpitelli (La Bretagne Linguistique, 2014)
This study was based on data taken from the linguistic atlases of the Channel/Atlantic area. Using motivational and interpretative maps, it attempts to show the areal diffusion of representations underpinning lexical creation. In addition to an onomasiological mapping, it focuses in particular on the operative concepts of border and linguistic area and on the lexical motivation lessons as developed by researchers of the two main multilingual atlantographic undertakings, the Atlas Linguarum Europae (ALE) and the Atlas Linguistique Roman (ALiR). Several comparisons between the Celtic and Romance areas are considered. These are based on the zoonyms for the earthworm, slug, sandworm, wrasse and cuttlefish. The overlaps and/or complementarities in certain Romance and Celtic domains shed light on lexical forms that have become opaque in the Romance linguistic area but are still transparent in the Celtic area, and vice versa.